The Poison Apple - Archer, Lily. (New York : Feiwel and Friends, 2007)
At an elite Massachusetts boarding school, three fifteen-year-old girls of very different backgrounds discover a common bond and form a club to plot revenge against their evil stepmothers.
Keywords: Stepmothers -- Juvenile fiction; Boarding schools -- Juvenile fiction; Schools -- Juvenile fiction; Revenge -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Stepmothers -- Fiction; Boarding schools -- Fiction; Schools -- Fiction; Revenge -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Massachusetts -- Juvenile fiction; Massachusetts -- Fiction; Young adult fiction